The hostage bride - Feather, Jane. (New York : Bantam Books, 1998)
A seventeen-year-old young lady encounters adventure and romance when she is kidnapped by a ruthless outlaw.
Keywords: Historical fiction; Kidnapping -- Fiction; Love stories; Man-woman relationships -- Fiction; Outlaws -- Fiction; London (England) -- Social life and customs -- 17th century -- Fiction; Love stories